2018
DOI: 10.1080/17483107.2018.1465602
|View full text |Cite
|
Sign up to set email alerts
|

Manual wheelchair propulsion on ramp slopes encountered when boarding public transit buses

Abstract: Ascending bus ramps require greater power and pushrim force on steeper ramp slopes, presenting a potential barrier to transportation accessibility. Given this finding, it is imperative that bus operators minimize ramp slope to assure MWC users are able to access LATVs. Implications for Rehabilitation Although transit bus ramps are intended to provide wheelchair access to public transportation, limitations in MWC user physical strength and function may prevent safe access. Transit bus ramp slopes encountered du… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
10
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(10 citation statements)
references
References 15 publications
0
10
0
Order By: Relevance
“…One study investigated the kinetics of both wheels using only one instrumented wheel mounted separately on the right and left sides in different trials [ 49 ]. Two of the ten studies which used only one instrumented wheel reported having mounted a matching "dummy" wheel on the opposite side to ensure inertial symmetry [ 7 , 13 ].…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations
“…One study investigated the kinetics of both wheels using only one instrumented wheel mounted separately on the right and left sides in different trials [ 49 ]. Two of the ten studies which used only one instrumented wheel reported having mounted a matching "dummy" wheel on the opposite side to ensure inertial symmetry [ 7 , 13 ].…”
Section: Resultsmentioning
confidence: 99%
“…overground), MWC speed was found to decrease with increasing slope. Contradictory results were obtained on cycle frequency: MWU tended to increase their cycle frequency with slope on a long ramp [ 24 ], whereas AB decreased cycle frequency with slope on a short ramp [ 7 , 48 ]. Moreover, when the MWC speed was constant across the different slope inclinations (speed imposed by the treadmill belt), cycle frequency tended to increase with increasing slope in SCI subjects [ 28 , 29 ], but was not affected with AB subjects [ 13 ].…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…In daily life, power output in wheelchair propulsion is the sum of internal and rolling resistance, gravitational force (up an incline or slope), and air friction. Recently, Bertocci et al presented a biomechanical delineation of different slopes for public buses and their effects on push biomechanics in seven novice non-wheelchair users [45].…”
Section: Environmental Ramp Design: a Simple Case For Supportive Techmentioning
confidence: 99%